National conference on tertiary education 2005 industrial training program : A reflective practicum / Sariwati Mohd Shariff - Mohd Shariff, Sariwati (Universiti Teknologi MARA Cawangan Pahang, 2005)
Universiti Teknologi MARA has incorporated industrial training or practicum in its curricular structure for most of its academic programs in the Faculty of Business Management. The objective of this practicum is to expose undergraduates to the realities of life in the working environment, and to synthesize knowledge acquired in formal education into practice. It is generally assumed that undergraduates have learnt and acquired work skills in the industry and yet there has been no definitive means to assess their learning and skills while on the job training. The current evaluation system on the undergraduates' performance and the practicum itself is unilateral from the industry. However, the cognitive, psychomotor and affective skills of the undergraduates need to be evaluated in order to determine whether the industrial training program is effective from the undergraduates' perspectives. It is a concern for the university to determine whether the industrial training is meeting its objectives with added values in learning for the undergraduates for future job employability. This paper attempts to look into the theoretical concepts of an effective industrial training program and how effective learning takes place in industrial training. Effective learning and an effective industrial training program share common elements: defined training objectives, good trainer, motivated learner, structured training program, the learning process and organizational culture. However, social context, experiences and reflective learning are three significant elements that constitute effective industrial training.